Sigma-1 receptor expression in the dorsal root ganglion: Reexamination using a highly specific antibody. (7th September 2016) - Mavlyutov, Timur A.; Duellman, Tyler; Kim, Hung Tae; Epstein, Miles L.; Leese, Charlotte; Davletov, Bazbek A.; Yang, Jay
Graphical abstract: Highlights: Sigma-1 receptor is abundant in DRG neuronal soma, but not in satellite cells. Sigma-1 receptor is absent in processes of DRG neurons. In DRG neurons, S1R targets endoplasmic reticulum, nuclear envelope, and plasma membrane. Abstract: Sigma-1 receptor (S1R) is a unique pluripotent modulator of living systems and has been reported to be associated with a number of neurological diseases including pathological pain. Intrathecal administration of S1R antagonists attenuates the pain behavior of rodents in both inflammatory and neuropathic pain models. However, the S1R localization in the spinal cord shows a selective ventral horn motor neuron distribution, suggesting the high likelihood of S1R in the dorsal root ganglion (DRG) mediating the pain relief by intrathecally administered drugs. Since primary afferents are the major component in the pain pathway, we examined the mouse and rat DRGs for the presence of the S1R. At both mRNA and protein levels, quantitative RT-PCR (qRT-PCR) and Western confirmed that the DRG contains greater S1R expression in comparison to spinal cord, cortex, or lung but less than liver. Using a custom-made highly specific antibody, we demonstrated the presence of a strong S1R immuno-fluorescence in all rat and mouse DRG neurons co-localizing with the Neuron-Specific Enolase (NSE) marker, but not in neural processes or GFAP-positive glial satellite cells. In addition, S1R was absent in afferent terminals in the skin and in the dorsal horn of the spinal cord. Using immuno-electron microscopy, we showed that S1R is detected in the nuclear envelope and endoplasmic reticulum (ER) of DRG cells. In contrast to other cells, S1R is also located directly at the plasma membrane of the DRG neurons. The presence of S1R in the nuclear envelope of all DRG neurons suggests an exciting potential role of S1R as a regulator of neuronal nuclear activities and/or gene expression, which may provide insight toward new molecular targets for modulating nociception at the level of primary afferent neurons.